The Legal Consequences of Applying the Principle of Balance to Grant Agreements Waarmarked by Notaries - Soedijono, Agam (TABELLIUS: Journal of Law, 2023)
The development of contract law gave birth to a new principle, namely the principle of balance which states that an agreement is binding as long as it is based on a balance of interests between the parties. Agreement law in Indonesia recognizes grant agreements, namely unilateral agreements that only show the achievements of one party. The emergence of the principle of balance then raises issues which are the main focus of writing this law, related to the application and legal consequences in the grant agreement Number: 536/Waarmer/IV/201, April 6, 202 Notary PPAT Arif Indra Setyadi SH. MKn. Although there are no provisions governing the application of the principle of balance in Indonesian contract law, the application of the principle of balance is indirectly contained in Article 1320 of the Civil Code. The emphasis is on "agreement", "execution in good faith" and the binding agreement with "decency, custom and law" shows that in an agreement there should be a balance between the parties so as to create a sense of justice. An unbalanced agreement does not have binding power because it is contrary to good faith, a sense of justice and propriety. As a result, an unbalanced agreement can be requested for cancellation of the agreement.Keywords: Agreement; Balance; Grant; Waarmerking.